FAST ALGORITHMS AND COMPUTING MEANS OF CRYPTOLOGICAL FUNCTIONS - Horpenyuk, Andriy (International Journal of Computing, 2014)
The problems of speed of asymmetric cryptology computational algorithms are analyzed in the article. There has been offered for the greater speed to apply computing facilities of analytical principle of functioning together with algorithmic computing facilities. There have been given fundamentals of synthesis of such facilities, considered problems that limit domain of their application in cryptography. There have been given research results, which expose the prospects of application domain expansion of such facilities.